2020
DOI: 10.1038/s41598-020-63200-7
|View full text |Cite
|
Sign up to set email alerts
|

A novel diagnostic system to evaluate epidermal growth factor receptor impact as a prognostic and therapeutic indicator for lung adenocarcinoma

Abstract: Many driver pathways for cancer cell proliferation have been reported. Driver pathway activation is often evaluated based on a single hotspot mutation such as EGFR L858R. However, because of complex intratumoral networks, the impact of a driver pathway cannot be predicted based on only a single gene mutation. Here, we developed a novel diagnostic system named the "eGfR impact score" which is based on multiplex mRNA expression profiles, which can predict the impact of the EGFR pathway in lung cancer cells and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Supporting the notion of distinguished EGFR and fusion aberrations, our transcriptomic analysis demonstrated that MPE-derived cell lines were subtyped in parallel with the genetic aberrations. The transcriptomic subtyping of EGFR-mutant NSCLC has been performed in other studies as well 28 , 29 . Our study has demonstrated that MPE-derived NSCLC cell lines also retain the transcriptional characteristics of EGFR-mutant NSCLC, which were distinctive to NSCLC cell lines with other driver mutations such as KRAS or fusion genes.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting the notion of distinguished EGFR and fusion aberrations, our transcriptomic analysis demonstrated that MPE-derived cell lines were subtyped in parallel with the genetic aberrations. The transcriptomic subtyping of EGFR-mutant NSCLC has been performed in other studies as well 28 , 29 . Our study has demonstrated that MPE-derived NSCLC cell lines also retain the transcriptional characteristics of EGFR-mutant NSCLC, which were distinctive to NSCLC cell lines with other driver mutations such as KRAS or fusion genes.…”
Section: Discussionmentioning
confidence: 99%